PENGARUH REWARD DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PERSONEL KEPOLISIAN RESORT (POLRES) PAMEKASAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL MEDIASI - Novi Sulistya; Subijanto; Woro Utari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
Abstract The results showed that: 1) Reward had a significant positive effect on work performance with an original sample value of 0.566. 2) Reward has a significant positive effect on organizational citizenship behavior with the original sample value of 0.330. 3) Work discipline has a significant positive effect on work performance with the original sample value of 0.643. 4) Work discipline has a significant positive effect on organizational citizenship behavior with an original sample value of 0.632. 5) Organizational citizenship behavior has a significant negative effect on work performance with an original sample value of -0.196. 6) Reward has no significant negative effect on work performance mediated by organizational citizenship behavior with an original sample value of -0.065. 7) Work discipline has a significant negative effect on work performance mediated by organizational citizenship behavior with an original sample value of -0.124.